CULTURAL COMPETENCE, IMPLEMENTATION CHALLENGES, AND PROFESSIONAL GROWTH PERCEPTIONS AMONG TEACHING INTERNS IN DIVERSE CLASSROOMS - Cyrus Pontawe Casingal; Debbie Joyce Dudang Quimson; Liza Lanuza Quimson (EDUCATIONE, 2026)
Teaching internships place preservice teachers in settings where linguistic and cultural diversity must be addressed in daily instruction, yet evidence remains limited on how interns simultaneously perceive their cultural competence, implementation challenges, support resources, and professional growth in a Philippine provincial context. This study aimed to describe these interrelated perceptions among 91 Bachelor of Elementary Education teaching interns at Pangasinan State University-San Carlos Campus. A cross-sectional concurrent embedded mixed-methods survey was used. Quantitative responses to 5-point self-report items were summarized using frequencies, percentages, means, and standard deviations, while open-ended responses supplied descriptive qualitative context. Self-ratings were highest for understanding how cultural differences affect teaching and learning (M = 4.42, SD = 0.68) and lowest for perceived effectiveness in cross-cultural communication (M = 4.04, SD = 0.82). Challenge ratings ranged from M = 3.13 to M = 3.47, with the highest mean for understanding and addressing cultural differences in the classroom. Pre-internship orientation was selected as helpful by 86.8% of respondents, whereas 39.6% rarely or never sought mentor guidance. Perceived internship-outcome ratings ranged from M = 4.47 to M = 4.71. Open-ended responses illustrated language barriers, inclusive strategies, cultural-protocol concerns, and perceived identity development. Favorable self-perceptions therefore coexisted with continuing implementation difficulty. The findings support targeted mentoring and practice-focused preparation but remain descriptive and context-bound because participant-flow, instrument-validation, and qualitative-coding documentation were incomplete.